The Rise and Fall of Osama Bin Laden - Bergen, Peter L. (Simon & Schuster, 2021)
Intro -- Title Page -- Dedication -- A Note on Transliteration -- Bin Laden Family Tree -- Prologue: Hopes and Dreams and Fears -- Part I: Holy Warrior -- Chapter 1: Sphinx Without a Riddle? -- Chapter 2: Zealot -- Chapter 3: Jihad -- Chapter 4: Al-Qaeda -- Part II: War with the U.S. -- Chapter 5: Radical -- Chapter 6: "The Head of the Snake" -- Chapter 7: A Declaration of War -- Chapter 8: The U.S. Slowly Grasps the Threat -- Chapter 9: The War Begins -- Chapter 10: The Road to 9/11 -- Part III: On the Run -- Chapter 11: Triking Back -- Chapter 12: The Great Escape -- Chapter 13: Al-Qaeda Revives -- Chapter 14: The Hunt -- Chapter 15: A Lion in Winter -- Chapter 16: Operation Neptune Spear -- Chapter 17: After bin Laden -- Photographs -- Acknowledgments -- About the Author -- A Note on Sources -- Notes -- Selected Bibliography -- Index -- Copyright.